DAYA DUKUNG EKOLOGIS DAN JUMLAH WISATAWAN DI KAWASAN WISATA TAMAN HUTAN RAYA SULTAN ADAM MANDIANGIN KALIMANTAN SELATAN - Mitha Permata Amelia; Fonny Rianawati; Arfa Agustina Rezekiah (Universitas Lambung Mangkurat, 2021)
The ecological carrying capacity of the tourist area is needed for the ability of the area to accommodate a certain number of tourists without causing a decrease in the physical quality of the environment. This study aims to calculate the number of tourist visits to travel in one period and calculate the ecological carrying capacity of tourism Sultan Adam Mandiangin Forest Park tourism. The method of determining the sample of research respondents used the accidental sampling method with the number of selected tourist respondents of 99 respondents and respondents for the management of this tourist area were 11 people. Sampling was conducted using structured interview techniques using a questionnaire and observation methods around the tour. Data analysis was performed by calculating tourist visits carried out in one period (1 year) represented by intensive sample counting of visits for 1 month (30 days), the needs of tourist areas and the carrying capacity of the area. The results of the amount tourism and the ecological tourism carrying capacity are the number of tourist visits in 2017 to 2019 with 83,285 people, 81,430 and 89,480 people and the ecological carrying capacity of tourism which is 17 people per hectare and the area needs of each tourist is 588 m², meaning the number of tourists visiting to the Sultan Adam Mandiangin Forest Park area is still small and the level of damage caused is still lowDaya dukung ekologis kawasan wisata diperlukan untuk kemampuan area menampung wisatawan dalam jumlah tertentu tanpa mengakibatkan penurunan kualitas fisik lingkungan. Penelitian ini bertujuan untuk menghitung jumlah kunjungan wisatawan untuk berwisata dalam satu periode dan menghitung daya dukung ekologis wisata Taman Hutan Raya Sultan Adam Mandiangin. Metode penentuan sampel responden penelitian menggunakan metode accidental sampling dengan jumlah responden wisatawan terpilih sebanyak 99 responden dan responden untuk pengelola kawasan wisata ini adalah sebanyak 11 orang. Pengambilan sampel dilakukan dengan menggunakan teknik wawancara terstruktur menggunakan Kuesioner dan metode observasi sekitar wisata. Analisis data dilakukan dengan penghitungan kunjungan wisatawan dilakukan dalam satu periode (1 tahun) yang diwakili penghitungan sampel intensif kunjungan selama 1 bulan (30 hari), kebutuhan area wisata dan daya dukung kawasan. Hasil penelitian jumlah wisatawan dan daya dukung ekologis wisata yaitu jumlah kunjungan wisatawan tahun 2017 sampai 2019 dengan 83.285 orang, 81.430 dan 89.480 orang dan kapasitas daya dukung ekologis wisata yaitu 17 orang per hektar dan kebutuhan area setiap wisatawan yaitu 588 m², artinya jumlah wisatawan yang berkunjung ke kawasan Taman Hutan Raya Sultan Adam Mandiangin masih sedikit dan tingkat kerusakan yang diakibatkan masih rendah